Exposure-Response Relationship of Certolizumab Pegol and Achievement of Low Disease Activity and Remission in Patients With Rheumatoid Arthritis - Stéphane Paul; Hubert Marotte; Arthur Kavanaugh; Philippe Goupille; Tore K. Kvien; Marc deLongueville; Denis Mulleman; William J. Sandborn; Niels Vande Casteele (Wiley, 2020)
Anti‐tumor necrosis factor (anti‐TNF) drugs are often prescribed for the treatment of rheumatoid arthritis (RA) and other immune‐mediated inflammatory diseases. Although this treatment has been shown to be effective in many patients, up to 40% of patients do not achieve disease control. Drug concentration in plasma may be a factor affecting the observed variability in therapeutic response. In this study, we aimed to identify the plasma concentrations of the anti‐TNF certolizumab pegol (CZP), associated with improvement in disease activity in patients with RA. Data were pooled from three randomized, controlled clinical trials with a combined total of 1,935 patients analyzed. Clinical outcomes of low disease activity (LDA) and remission were defined as Disease Activity Score in 28 joints with C‐reactive protein (DAS28(CRP)) ≤ 2.7 and < 2.3, respectively. Quartile analysis results indicated that there may be an exposure‒response relationship between CZP concentration and LDA/remission outcomes at weeks 12 and 24; the association was strongest for LDA (P < 0.05). Receiver operating characteristic (ROC) analysis showed that CZP concentrations ≥ 28.0 μg/ml at week 12, and ≥ 17.6 μg/ml at week 24, were associated with a greater likelihood of achieving LDA/remission outcomes. Although confirmatory studies are warranted to define the optimal CZP therapeutic range at weeks 12 and 24, these data indicate that CZP concentrations may be associated with improvement of disease activity.